ON THE EXISTENCE OF A TYPE OF RICCI-RECURRENT MANIFOLD - De, U. C.; De, B. K. (Matematichki Bilten, 2007)
In the present paper we study properties of Ricci-recurrent manifolds which satisfy certain conditions, and prove the existence of such manifolds by a non-trivial concrete example.